SAT0421 Location of Disk Herniation (Median or Lateral) Affects Clinical Features, but not the Outcome of Lumbar Radiculalgia in Patients without Lumbar Spinal Stenosis. (23rd January 2014) - Merot, O.; Le Goff, B.; Maugars, Y.; Berthelot, J.-M.
Abstract : Background: It has been claimed that lumbar radiculalgia induced by foraminal disk herniations had poorer outcomes and different clinical features, including: 1-more progressive onset; 2-more severe radiculalgia; 3-less frequent/severe back pain; 4-less limitation of straight leg raising (SLR); 5-more frequent neurological deficits; 6-poorer outcome (Ref 1). Objectives: We wished to check whether patients with median disk herniations but no spinal stenosis (either central of foraminal) had indeed different features and outcome than patients with more lateral disk herniations. Methods: Patients whose lumbar radiculalgia required hospitalization were included in this prospective study each time TDM or MRI had already been performed and showed a clear disk prolapsus or herniation, but no features of spinal stenosis (either central of foraminal). Disk herniations were classified as median, mostly located in recess, in foramen, or extra-foraminal. Patients with median disk herniations were then compared to patients with more lateral herniations, their outcome being assessed by a phone call using a standardized questionnaire, at least 6 months after baseline. Results: 59 patients (31 males) were included (49 sciatica): 31 (53%) had median disk herniations, and 28 (47%) more lateral herniations (within recess in 3, foraminal in 20, and extra-foraminal in 5). No significant differences according to the location of herniations were noticed for the speed of radiculalgia onset, back pain (both lying or standing), and leg pain (both lying or standing), but significant differences (t test < 0.05) were observed for other items: the 28 patients with more lateral herniations were 8 years older (53.4 +/- 15.8 Vs 45.2 +/- 12.6); their herniations involved disks from upper levels (above L4-L5: 7/28 Vs 3/31); motor weakness was more frequent (25% Vs 3%); SLR was less restricted (65.0 +/- 24.5° Vs 51.1 +/- 25.7°); DN4 score of neuropathic pain was higher (4.4 +/- 2.1 Vs 3.2 +/- 1.8); anxiety was higher (10.3 +/- 4.1 Vs 7.9 +/- 3.2); the use of opioids was more frequent (39% Vs 22%); length of hospital stay was longer (5.7 +/- 2.4 Vs 4.5 +/- 1.4 days); and physician's prognosis of a good outcome was poorer (6.6 +/-2.2 Vs 8.0 +/- 1.6). However, at the end of follow up (12.2 +/- 3.3 months) outcomes were similar: 37% (Vs 41% for median herniations) had transiently relapsed, 66% felt improved (Vs 63%), 27% felt cured (Vs 22%), and walking capacity was nearly identical (3.7 +/- 1.8 kms, Vs 4.1 +/- 1.6), despite only 21% had to be operated (Vs 37% of those with median herniations). Conclusions: Despite slight clinical differences, the outcome of radiculalgia induced by lateral lumbar disk herniations seems even better than the outcome of those induced by median disk herniations. Previous claims of poorer outcomes in foraminal herniations might be explained by the inclusion of patients with associated foraminal stenosis. Thus, surgery should not be requested earlier just because the disk herniation is more lateral, moreover as motor weakness had disappeared in all cases at the end of follow-up. References: Lejeune JP, et al. Spine (Phila Pa 1976) 1994:19:1905-8. Disclosure of Interest: None Declared